A cephalosporin–chemiluminescent conjugate increases beta-lactamase detection sensitivity by four orders of magnitude. Issue 24 (26th February 2020) - Maity, Santanu; Wang, Xiaojian; Das, Subhamoy; He, Maomao; Riley, Lee W.; Murthy, Niren
Abstract : A beta-lactamase chemiluminescent probe, termed CCP, which can for the first time detect beta-lactamase activity via chemiluminescence and 4-orders of magnitude higher than commercial fluorescent probe. Abstract : The expression of beta-lactamases in bacteria is a central cause of drug resistance. In this report, we present a beta-lactamase chemiluminescent probe, termed CCP, which can for the first time detect beta-lactamase activity via chemiluminescence and can detect beta lactamase with a sensitivity that is 4-orders of magnitude higher than the commercially available fluorescent lactamase substrate fluorocillin.